Solid fuel production with torrefaction from vineyard pruning waste - Duranay, Neslihan Deveci; Akkus, Gizem (Springer Heidelberg, 2021)
Viticulture has an important place in the agricultural structure of our country and makes an essential contribution to the national economy. After the pruning procedures are performed in the spring, huge amounts of waste vine shoots (WVS) are obtained. This biomass, which is mostly used as igniter due to its high volatile content, is not usually employed as fuel. This valuable biomass is accumulated in certain places in the countryside and is abandoned to decay. Producing solid fuels with better properties than parent biomass is a reasonable alternative to appraise these kinds of wastes. In this study, therefore, torrefaction of WVS was investigated using a vertical furnace. Torrefaction experiments were conducted in a poly-particle bed under nitrogen flow and at 220, 250, and 280 degrees C temperatures corresponding to light, mild, and severe conditions, respectively. Furthermore, the effect of the processing time on solid product yield was investigated. In order to determine the features of solid products and compare them with raw biomass, proximate, elemental, FTIR, thermogravimetric analysis (TGA), and differential thermal analysis (DTA) analyses were conducted, and higher heating values (HHV) were determined. It was observed that severe torrefaction (280 degrees C) conditions were suitable to improve the fuel properties of the torrefied WVS. The HHV of the WVS torrefied at 280 degrees C for 60 min increased from 17.8 to 24.4 MJ/kg. Fixed carbon contents of torrefied WVS increase with temperature, and their atomic O/C and H/C ratios approach to peat and lignin zone on the Van Krevelen diagram for severe torrefaction conditions. Torrefied biomass is thus more suitable to partially replace coals employed in industry. .
Keywords: Agricultural waste; Torrefaction; Higher heating values; Energy yield; Lignocellulosic structure